Adolescents’ perceptions about non-suicidal self-injury, suicidal ideation and suicide attempts - Duarte, Eva (2023)
Introduction: Non-suicidal self-injury, suicidal thoughts and behaviors present high prevalence rates in adolescence. Aims: This study aimed to describe adolescents’ perceptions about these phenomena, and to analyze and compare the differences of these perceptions among adolescents with and without a history of non-suicidal selfinjury, suicidal ideation, and suicide attempts. Methods: The convenience sample consisted of 452 adolescents in ages between 12 and 18 (M(SD) = 15.59(1.50), 48% male and 52% female. For data collection, the Free Association Test was used in a survey, and data was analyzed through content analysis. Results: Results showed that 10.8% of the participants presented a history of non-suicidal self-injury, 19.9% suicidal ideation, and 2.7% suicide attempts. Perceptions were grouped into eight dimensions: Consumption of Psychoactive Substances; Death/Suicide; Interpersonal Factors; Intrapersonal Factors; Moral Judgments; Negative Emotions; Psychological Functions; and Self-Injurious Methods. Further analysis revealed that adolescents with and without a history of non-suicidal self-injury, suicidal ideation, and suicide attempts presented differences in their perceptions of these phenomena. Conclusions: These findings contribute to the understanding regarding the perceptions of adolescents about these phenomena and might have implications regarding their prevention and intervention.